Technology-Enhanced STEM-PjBL: A Pathway to Strengthen Students’ Critical Thinking in Understanding the Nature of Science through Social Phenomena - Sukarno, Sukarno; Triani, Elza; Azzahra, Miftahul Zannah; Nawahdani, Ahmad Mansur (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of STEM-PjBL learning integrated with technology media on students' critical thinking skills on the material of the Nature of Science and Scientific Methods in the context of social phenomena, and to see the effectiveness of this approach in improving students' scientific reasoning. Methodology: The study used a mixed methods sequential explanatory design. Quantitative data were obtained through critical thinking tests and questionnaires, while qualitative data were obtained through interviews and observations. Analysis included normality, homogeneity, t-tests, ANOVA, and effect size tests using SPSS. Learning was supported by digital simulations, virtual experiment applications, and technological devices in the implementation of STEM-PjBL.. Main Findings: The results showed a significant increase in critical thinking skills in the experimental class compared to the control class. Posttest scores, gain scores, and effect size (d = 1.58) indicated a significant effect. Qualitative findings revealed increased student engagement, ability to interpret data through digital media, self-reflection, and more effective application of scientific methods during the project compared to conventional learning. Novelty/Originality of this study: This research offers novelty through the simultaneous integration of STEM-PjBL, interactive technology media, and basic material on the Nature of Science within the context of social phenomena, which has rarely been studied before. This study also simultaneously assesses critical thinking and science process skills, thus providing a new contribution to the development of technology-based science learning to strengthen students' scientific abilities.